Suicidal behaviours and moderator support in online health communities: protocol for a scoping review - Amanda Perry; Andrea Lamont-Mills; Carol du Plessis; Jan du Preez; Denise Pyle (BMJ Open)
Introduction Suicidal ideation and suicidal behaviours are common yet complex mental health presentations that can pose significant challenges for health professionals. The inability to accurately predict the individuals who may move from experiencing suicidal ideation and associated behaviours, to completing suicide, presents one such challenge. This can make it difficult to provide interventions and support to those most in need. Online health communities are one possible source of support for individuals who experience suicidal ideation and behaviours. These communities are becoming an increasingly popular way of accessing support, often with life-saving consequences. Within online communities, support is offered by various individuals including, in some instances, health professionals from various backgrounds, who work as online health community moderators. Given the growth of online communities and the increasing number of health professionals working as moderators, this scoping review seeks to map the literature that has focused on health professionals working as online community moderators, who interact with members experiencing suicidal ideation and behaviours. Mapping the existing literature offers benefits to both research and practice by identifying gaps in the research and providing a beginning knowledge base of current practice that can inform the training and development of health professionals working as community moderators.Methods and analysis This scoping review will follow the methodological framework of Arksey and O’Malley, later adapted by Levac et al. To ensure appropriate rigour, this protocol uses the 20-item Preferred Reporting Items for Systematic Reviews and Meta-Analyses and extension for Scoping Reviews. Literature will be identified using a search strategy developed in consultation with a specialist research librarian at the university where the researchers are employed. Ten multidisciplinary databases will be independently searched by two researchers, and both researchers will screen for inclusion, and undertake the data extraction. The first author will perform a quality assessment of the articles that are selected for inclusion. A second researcher will complete a random audit of 20% of the included articles to assess for quality and suitability in answering the research questions. The first author will complete the analysis and synthesis of the data. A numerical and narrative synthesis of the included studies will be provided.Ethics and dissemination The scoping review has been deemed as being exempt from ethical review as no data will be collected from human participants. The results of the scoping review may be published in a peer-reviewed journal, thesis, presented at relevant conferences, and shared with relevant knowledge users.